1993
DOI: 10.1126/science.7901913
|View full text |Cite
|
Sign up to set email alerts
|

Structural Basis of Pilus Subunit Recognition by the PaPd Chaperone

Abstract: The assembly of different types of virulence-associated surface fibers called pili in Gram-negative bacteria requires periplasmic chaperones. PapD is the prototype member of the periplasmic chaperone family, and the structural basis of its interactions with pilus subunits was investigated. Peptides corresponding to the carboxyl terminus of pilus subunits bound PapD and blocked the ability of PapD to bind to the pilus adhesin PapG in vitro. The crystal structure of PapD complexed to the PapG carboxyl-terminal p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

11
220
0

Year Published

1995
1995
2012
2012

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 213 publications
(231 citation statements)
references
References 44 publications
11
220
0
Order By: Relevance
“…Specialized complex structures in cells often need their own ''dedicated'' chaperones (e.g., ref. 49).…”
Section: Resultsmentioning
confidence: 99%
“…Specialized complex structures in cells often need their own ''dedicated'' chaperones (e.g., ref. 49).…”
Section: Resultsmentioning
confidence: 99%
“…Another key binding motif, first identified in the complex between the PapD chaperone and a C-terminal peptide of the subunit PapG 40 , is the C-terminal F strand of the pilin domain. This F strandchaperone interaction is also conserved in all structures of FimCsubunit complexes 1,25,26 .…”
Section: Discussionmentioning
confidence: 99%
“…In addition, the carboxyl group of the C-terminal Gln159 forms two salt bridges with Arg8 and Lys112, two invariant residues located in the interdomain cleft of the chaperone. Mutations of the corresponding residues studied in PapD, a close homolog of FimC, revealed that both residues are critical for pilus subunit binding 40 . The N-terminal region of FimA t , including the A′ strand, interacts with residues 1-7 of FimC, whereas the A′ strand forms an antiparallel β-sheet with the G strand of FimC.…”
Section: Fimc-fima T Structurementioning
confidence: 99%
“…The PapG adhesin is degraded in the periplasm, if expressed in the absence of PapD [6]. Co-expression of the chaperone stabilizes the adhesin in a native-like conformation in a PapD^PapG periplasmic complex.…”
Section: Binding Of P Pili and Papd^papg Adhesin Complex To Mvm And Slpmentioning
confidence: 99%
“…The assembly of P pili requires the PapD immunoglobulin-like chaperone, which binds nascently translocated subunits via a L-zipper recognition paradigm. This interaction facilitates the release of subunits from the cytoplasmic membrane as soluble periplasmic chaperoneŝ ubunit complexes [5,6]. The chaperone^subunit complexes are then escorted to outer membrane assembly sites comprised of PapC where the complexes are dissociated and the subunits are incorporated into pili across the outer membrane [7].…”
Section: Introductionmentioning
confidence: 99%